2011
DOI: 10.1055/s-0031-1275277
|View full text |Cite
|
Sign up to set email alerts
|

Do Persons that Changed Health Insurance Differ From those Who did not? The Case of Diabetes

Abstract: Persons that changed their fund had a much lower prevalence of diabetes than those who did not. Most of this difference could be explained by age. We found quite similar figures for hypertension, a more prevalent disease. However, ORs were significant in all described models, probably due to a higher statistical power.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
2
7
0
Order By: Relevance
“…However, a very high proportion of cases and controls were continuously insured with the AOK NordWest. This finding is well in line with results of a study conducted by Hoffmann and Icks . Sixth, no adjustment for multiple testing was performed.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, a very high proportion of cases and controls were continuously insured with the AOK NordWest. This finding is well in line with results of a study conducted by Hoffmann and Icks . Sixth, no adjustment for multiple testing was performed.…”
Section: Discussionsupporting
confidence: 89%
“…This finding is well in line with results of a study conducted by Hoffmann and Icks. (34) Sixth, no adjustment for multiple testing was performed. Some significant tests might be inflated by chance.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…Person-years were aggregated for all insured persons aged 60 years or older and at risk of having a first pelvic fracture. Most persons were continuously insured with the AOK N ord W est, which is in line with results of a study conducted by Hoffmann and Icks [ 37 ]. Therefore, person-years per calendar year should resemble persons in a very adequate manner.…”
Section: Discussionsupporting
confidence: 87%
“…A previous study demonstrated that people who change their insurance company are younger, better educated, and have a lower prevalence of diabetes and cardiovascular disease. 42 As a consequence, our study population was somewhat older than the general German population, which was particularly true for women (proportion in 2010: 5.4% women over 80 years in our data set vs 3.5% women over 80 years in the whole of Germany; 2.1% men over 80 years in our data set vs 1.7% men over 80 years in the whole of Germany). However, the prevalence of diabetes in our study was well in line with recently published nationwide data.…”
Section: Discussionmentioning
confidence: 73%